Dynamic Relationship between Human Capital and Economic Growth in Sri Lanka: A Co-Integration Analysis - Vijesandiran, S.; Vinayagathasan, T. (Growth, 2015)
Annual data from Sri Lanka was used to analyze dynamic linkage between human capital and economic growth rate. ADF, PP, and Ng-Perron unit root tests confirmed that all the series that has been included in the model are stationary at first difference. Co-integration test identified one co-integrating vector, suggesting long-run relationship between the variables. Both co-integration and VECM test revealed a positive long-run relationship between health index and per capita GDP. We also found the long-run equilibrium of the model for the real per capita GDP, real capital expenditure on human capital and real labor expenditure on human capital. The results of VECM suggested a short-term relationship between per capita GDP and health care, education level and per capita income and health care and education.